Gestión del Conocimiento de Social Media Marketing, para Aumentar las Ventas de las Micro-empresas de Servicios, Cuyos Clientes son Parte de una Comunidad Universitaria. Caso Ciudad de Puebla (2020)
Social networks offer important benefits marketing terms, among the most important is the detailed markets segmentation and low publicity costs. Despite this, SMEs, which represent a high index in Mexico, do not have the knowledge to fully exploit the benefits of social media marketing. The objective of the article was to propose effective strategies for the implementation of social media marketing, to increase sales in service SMEs that have as potential clients, university communities. The present investigation used a simple descriptive correlational design, interviews were conducted with micro-business owners and a 7-question quizz applied to the university community (potential clients) Among the main results, it was found that the university community uses social networks little with purchase objectives, and in the cases in which they have bought, they have been tangible products but not services. Therefore, in the article conclussions, specific strategies applicable to service SMEs are presented, which in turn can be translated into increased sales.